Capped carbon nanotubes with a number of ground state magnetization discontinuities increasing with their size*Dedicated to the memory of Dr. Brahim Belhadji. (24th April 2017) - Konstantinidis, N P
Abstract: The classical ground state magnetic response of fullerene molecules that resemble capped carbon nanotubes is calculated within the framework of the antiferromagnetic Heisenberg model. It is found that the magnetic response depends subtly on spatial symmetry and chirality. Clusters based on armchair carbon nanotubes which are capped with non-neighboring pentagons and have D 5 d spatial symmetry have a number of magnetization discontinuities which increases with their size. This occurs even though the model completely lacks magnetic anisotropy, and even though the only source of frustration are the two groups of six pentagons located at the ends of the molecules, which become more strongly outnumbered as the clusters are filled in the middle with more unfrustrated hexagons with increasing size. For the cluster with 180 vertices there are already seven magnetization and one susceptibility discontinuities. Contrary to that, similar molecules which have D 5 h spatial symmetry reach a limit of one magnetization and two susceptibility ground state discontinuities, while fullerene molecules based on zigzag carbon nanotubes and capped by neighboring pentagons also reach a fixed number of discontinuities with increasing size.